Multi-scale-filler reinforcement strategy enabled stretchable silicone elastomer with synergistically enhanced thermal conductivity and mechanical strength - Tan, Junrui; Zhu, Guizhi; Yang, Fengxia; Zhang, Siyi; Wu, Qiong; Xu, Linli; Li, Yong; Tan, Longfei; Meng, Xianwei; Yu, Jinhong; Li, Laifeng (Composites. Part A, Applied science and manufacturing, 2023)
As soft electronic devices and robotics advance towards high power density and miniaturization, integrating superior thermal and mechanical properties has become a big challenge for functional elastomers. Herein, a multi-scale-filler reinforcement strategy was reported for constructing stretchable, mechanically strengthened and thermally conductive silicone elastomers. The multi-scaled Al₂O₃/vinyl and methyl co-modified fumed SiO₂ (VM-SiO₂) co-filled liquid silicone rubber composite exhibited a high thermal conductivity of 1.25 W m⁻¹ K⁻¹ at ∼55 vol% filler loading, 555.7% higher than that of the matrix. The finite element simulation demonstrated that the “bridging” effect of small-scaled fillers between gaps of large-scaled spheres in the matrix lowered the interfacial thermal resistance. Meanwhile, stemming from the strong interfacial interactions between the VM-SiO₂ and matrix, up to 12.4 times higher elongation at break (7.17%) and 317.7% increase of tensile strength (3.00 MPa) were reached. We further demonstrated the potential application of the multi-scaled Al₂O₃/VM-SiO₂ co-filled LSR composites for thermal management materials.